2001
DOI: 10.1021/ja011175r
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR Investigation of the Influence of Nonligated Residue Contacts on the Heme Electronic Structure in Cyanometmyoglobin Complexes Reconstituted with Centro- and Pseudocentrosymmetric Hemins

Abstract: The 1H and 13C chemical shifts for the heme methyls of low-spin, ferric sperm whale cyanometmyoglobin reconstituted with a variety of centrosymmetric and pseudocentrosymmetric hemins have been recorded and analyzed to shed light on the nature of heme-protein contacts, other than that of the axial His, that modulate the rhombic perturbation to the heme's in-plane electronic asymmetry. The very similar 1H dipolar shifts for heme pocket residues in all complexes yield essentially the same magnetic axes as in wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…These authors demonstrated that even if the magnetic axes and anisotropies are known, the intrinsic uncertainties in the orientational parameters lead to a relatively large uncertainty in the determination of the dipolar contribution to the methyl proton isotropic shifts. By comparison, the relatively small contribution of the methyl carbon dipolar shift to the isotropic shift makes the methyl carbon contact shifts more reliable indicators of the unpaired electron distribution on the heme macrocycle [114,131]. Thus, by utilizing the 13 CH 3 pattern of non-inversion symmetry in centro-and pseudocentro-symmetric hemes reconstituted into myoglobin, it was shown that π-1480 Fig.…”
Section: Nmr Shifts Axial Ligands and Axial Ligand Geometrymentioning
confidence: 96%
See 2 more Smart Citations
“…These authors demonstrated that even if the magnetic axes and anisotropies are known, the intrinsic uncertainties in the orientational parameters lead to a relatively large uncertainty in the determination of the dipolar contribution to the methyl proton isotropic shifts. By comparison, the relatively small contribution of the methyl carbon dipolar shift to the isotropic shift makes the methyl carbon contact shifts more reliable indicators of the unpaired electron distribution on the heme macrocycle [114,131]. Thus, by utilizing the 13 CH 3 pattern of non-inversion symmetry in centro-and pseudocentro-symmetric hemes reconstituted into myoglobin, it was shown that π-1480 Fig.…”
Section: Nmr Shifts Axial Ligands and Axial Ligand Geometrymentioning
confidence: 96%
“…Other factors such as the nature of heme substituents (i.e., vinyl, methyl, and propionate), van der Waals interactions between the heme and side chains lining the heme pocket, and heme conformational distortions from planarity can provide secondary modifications of the in-plane asymmetry. A recent study pointed out that 13 C NMR spectroscopy is well suited to elucidate the nature and extent of these secondary regulatory mechanisms [131]. These authors demonstrated that even if the magnetic axes and anisotropies are known, the intrinsic uncertainties in the orientational parameters lead to a relatively large uncertainty in the determination of the dipolar contribution to the methyl proton isotropic shifts.…”
Section: Nmr Shifts Axial Ligands and Axial Ligand Geometrymentioning
confidence: 98%
See 1 more Smart Citation
“…Lastly, it is observed that each of the meso-Hs exhibit 2-4 ppm low-field d con , as previously observed for sperm whale metMbCN (29), which is contrary to the difference in the a-/ d-meso versus b-/d-meso-H d con as predicted ( 18) by the prevailing model for hyperfine shifts in low-spin ferric hemins. The failure to account for meso-H d con patterns in other metMbCN complexes has been noted previously (52). Detailed calculations of the unpaired spin distribution in low-spin ferric hemes have shown that correlation leads to both positive and negative spin density on the heme periphery that cannot be interpreted simply based on MO theory of p-spin density in a single molecular orbital (53) .…”
Section: Electronic Structurementioning
confidence: 95%
“…δH=δHdia+δHcon+δHpcM δC=δCdia+δCconπ+δCpcM+δCpcLπ where δ H dia and δ C dia are the shifts of the same nuclei in a diamagnetic complex (usually Zn(II)-substituted complexes are used to evaluate these27,39–41), δ H con is the proton contact shift contribution, and δ C conπ is the corresponding carbon contact shift for delocalization of the unpaired electron from the metal to the ligand through π bonds. The pseudocontact (formerly called dipolar39,40) shifts, δ H pcM and δ C pcM , are the result of the through-space dipolar coupling between the nucleus of interest (H or C) and the electron, which is centered on the metal, because of the magnetic anisotropy of d-orbitals, which produce an angular and distance dependence on the size of the pseudocontact shift and can be calculated if one knows the distance and angular relationship between each nucleus and the metal center from the X-ray crystal structure 24,39–41.…”
Section: Introductionmentioning
confidence: 99%